The Mediating Role of Job Satisfaction between Leadership Style and Performance of Academic Staff - Jameel , Alaa S. (International Journal of Psychosocial Rehabilitation, 2020)
Leadership style (LS) has not been effectively examined in educational institution in developing countries. The purpose of this study is to examine the effect of LS on academic staff performance (ASP) in Iraq. Based on the review, the study proposed that LS and its components; transformational leadership (TFL) and transactional leadership (TSL) will affect ASP. In addition, the study proposed job satisfaction (JS) as a mediator between LS, TFL, TSL, and ASP. Methodology The population of this study is the Iraqi academic staff in Baghdad. A stratified sampling technique was deployed to collect 297 responses from nine universities in Baghdad. The findings showed that LS, TFL and TSL have significant effect on ASP. JS mediated partially the effect of LS, TFL and TSL on ASP. Decision makers are advised to implement the TFL and increase the JS among academic staff.